1999
DOI: 10.1029/1998rs900012
|View full text |Cite
|
Sign up to set email alerts
|

New narrow‐beam meteor radar results at Christmas Island: Implications for diurnal wind estimation

Abstract: Abstract. Solar heating of the atmosphere is responsible for most of the diurnal oscillations in the neutral wind velocities and temperatures of the mesosphere and lower thermosphere. When these oscillations are global-scale waves, they are called atmospheric tides. Excited in the lower atmosphere, tides can propagate up into the upper atmosphere where they can break and deposit considerable energy and momentum into the mean flow. Ground-based estimates of the diurnal winds over Christmas Island have been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…However, these studies were performed at an altitude of 105 km, well within the E region, and were performed for equatorial conditions. Only one study has yet shown any support for such contamination [Chang et al, 1999], and that was also at the equator. Thus both such studies were for high-altitude equatorial conditions, and any similar effects at the poles are unknown.…”
Section: Instrumentationmentioning
confidence: 99%
“…However, these studies were performed at an altitude of 105 km, well within the E region, and were performed for equatorial conditions. Only one study has yet shown any support for such contamination [Chang et al, 1999], and that was also at the equator. Thus both such studies were for high-altitude equatorial conditions, and any similar effects at the poles are unknown.…”
Section: Instrumentationmentioning
confidence: 99%
“…In this scenario, the same caution that Briggs [1977] made for spaced receiver experiments applies to the meteor systems operating in the vicinity of the magnetic equator. In the light of the previous report based on the meteor radar observations made from Christmas Island by Chang et al [1999], we remind the readers of the potential problems in making reliable neutral wind measurements with radar systems probing the electrojet heights.…”
mentioning
confidence: 97%
“…MF, meteor and MST radars are being used to measure neutral winds in the mesosphere–lower thermosphere (MLT) region (80–100 km) with the advantage of continuous observation over a particular site. Radars operating near the magnetic equator have complexities in interpreting the measurements in terms of neutral wind, since the plasma drifts at electrojet heights are expected to contaminate neutral wind measurements [ Briggs , 1977; Chang et al , 1999; Gurubaran and Rajaram , 2000]. In this context we revisit the interpretations made by Kumar et al [2007], in particular, the affirmation that the meteor system makes reliable wind measurements at heights above 90 km.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DG09 refer to Chapin and Kudeki [1994], Chang et al [1999], and Oppenheim et al [2000] in the context of irregularities that grow on the trail as a result of plasma instabilities. The study carried out by Chapin and Kudeki [1994] deals with long‐lived nonspecular meteor echoes, which are not considered for the wind estimation by the meteor radars.…”
Section: Eej and The Neutral Windsmentioning
confidence: 99%